Role of Serum creatinine in forecasting the outcome after cardiac surgery beyond acute kidney injury-A Cross sectional Study - DIVYA DHARSHINI B; SMITA PADHY; GIRIJAVANI D S S; PAYALA VIJAYA LAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Acute kidney damage (Acute kidney injury [AKI]) is defined by elevations in serum creatinine levels that occur after surgery. In cardiac surgery, creatinine is a critical determinant. This study highlights the detection of serum creatinine as an early diagnostic and predictive marker of AKI following coronary artery bypass grafting (CABG) and to estimate the serum creatinine concentrations before and at 24 and 48 h after CABG. Methods: It is a single center, Cross-sectional study. Patients from Cardiothoracic and Vascular surgery undergoing CABG in Sri Ramachandra Medical College and Research Institute were included in the study. A total of 80 cases were included in the study. The method used for measurement of serum creatinine is by modification of kinetic Jaffe reaction. Data were analyzed using Stata/SE version 16.0 and represented in terms of means, standard deviation at 95% confidence level and t’ test was performed as statistical analysis and p<0.05 indicates significance. Sigma plot software version 10.0 was used to draw the standard error mean graphs. Results: The serum creatinine values at 24 h after the surgery was statistically higher than the preoperative values at 5% significance level (p=0.04). The serum creatinine values 48 h after the surgery was also statistically higher than the preoperative values at 1% significance level (p=0.001). The serum creatinine values 48 h after surgery are highly significant (p=0.001) when compared to the serum creatinine values 24 h after surgery. Conclusion: Before an increase in serum creatinine level is detected, over 50% of renal function must be lost. It was concluded that serum creatinine is an inadequate and delayed marker of AKI.